#TITLE_ALTERNATIVE# - NURUDDIN (NIM : 12208068), MUKHAMMAD
Coalbed methane reservoir is belongs to naturally fractured reservoirs. Naturally fractured reservoirs have permeability value that is very sensitive with stress change or pore pressure. Drawdown that occurred during production will increase the effective stress so that it will decrease the value of rock permeability. In contrast, negative drawdown that occurred during injection will decrease the effective stress so that it will increase the value of rock permeability. Various models of permeability changehave been developed to analyze the stress-dependent permeability. In this thesis, Palmer and Mansoori model is used to analyze the permeability changes that occur as a result of stress-dependent permeability. Palmer and Mansoori model gives the relationship between the ratio of permeability changeas a function of rock mechanic parameters and pore pressure change. Consequently, the value of pore pressure is needed to find out the change in permeability. Therefore, this thesis proposes an equation which can directly describethe relationship between the ratio of permeability changeand the pressure drawdown based on numerical models built using thepermeability change model of Palmer and Mansoori.